Post-operative Analgesia in Arthroscopic knee surgery: a comparison between Intra-Articular Clonidine and Dexmedetomidine - Biswas, Chaitali; Roy, Amrita; Bhattacharjee, Dhurjoti Prosad; Paul, Suhrita (Eastern Journal of Medical Sciences, 2019)
Background: Arthroscopic surgery is associated with variable amount of postoperative pain and sometimes the pain is considerable. To provide postoperative analgesia after arthroscopic knee surgery, various medications have been administered intra-articularly. Aim: To compare the postoperative analgesic effects of intra-articular clonidine and dexmedetomidine administered as adjuvants with local anesthetic levobupivacaine in patients undergoing arthroscopic knee surgery. Methods: Sixty patients undergoing elective knee arthroscopy were randomly assigned to one of the following groups containing 20 patients each. Group L patients received 19 ml of 0.25% levobupivacaine and 1 ml of isotonic saline (20 ml in total) intra-articularly. Group C patients received 150µg [1ml] of clonidine added to 19 ml of 0.25% levobupivacaine intra-articularly (total volume 20 ml). Group D patients received 100 µg (1 ml) of dexmedetomidine added to 19 ml of 0.25% levobupivacaine intra-articularly (total volume 20 ml). Analgesic effect was evaluated by measuring pain intensity (VAS score) and duration of analgesia. Results: A longer delay was observed between intra-articular injection of study medication and first requirement of supplementary analgesic in group C (10.44 ± 4.6 hours) and in group D (10.72 ± 5.6 hours) compared to group L (6.18 ± 1.8 hours). Total consumption of diclofenac sodium in first 24 hours in postoperative period was significantly less in group C and D. No significant side effects were noted. Conclusion: Both clonidine and dexmedetomidine, added as adjuncts to levobupivacaine in patients undergoing arthroscopic knee surgery, improve the quality and duration of post operative analgesia.